Comparison of Efficacy between Single and Double Doses of Intravenous Ceftriaxone in The Treatment of Enteric Fever (The Planet, 2023)
Background: Typhoid fever is a serious global publichealth concern with a significant impact on developingcountries. The emergence of multi-drug resistant strains ofthe bacteria responsible for typhoid fever has madetreatment challenging. The present study aimed to comparethe efficacy of single and double doses of intravenousceftriaxone in the treatment of enteric fever. Methods andmaterials: This Randomized Controlled Trial (RCT) studywas conducted at the Department of Pediatrics atBangabandhu Sheikh Mujib Medical University in Dhaka,Bangladesh. The study duration was from July 07 to Jan08, 2018 with a total of 50 participants. Results: 28%were in the 4-6 age range, and 30% were from ≥10 agerange. 52% male participants were observed. Fever wasobserved in all the participants. 56% of group A had pakkahouse compared to 38% of group B. Diagnostic results revealed a higher prevalence ofpositive Widal tests in Group A (92.0%) and positive blood cultures for enteric fever inGroup B (36.0%). Although anorexia was significantly more common in Group A, nosignificant differences were found in age, gender, housing conditions, clinical signs, ordefervescence time, which averaged 4.0 days for Group A and 4.52 days for Group B.Conclusions: The study indicates that S. typhi strains were susceptible to ceftriaxone, and both single-dose and double dose ceftriaxone therapy were effective in treating enteric feverin pediatric patients. Therefore, a single dose of ceftriaxone can be considered an effectivetreatment option for enteric fever in pediatric patients.
Keywords: Ceftriaxone; Enteric-fever; Salmonella-typhi